2001
DOI: 10.4049/jimmunol.166.9.5550
|View full text |Cite
|
Sign up to set email alerts
|

The Vasodilator-Stimulated Phosphoprotein Is Regulated by Cyclic GMP-Dependent Protein Kinase During Neutrophil Spreading

Abstract: The expression and phosphorylation state of the vasodilator-stimulated phosphoprotein (VASP), a membrane-associated focal adhesion protein, was investigated in human neutrophils. Adhesion and spreading of neutrophils induced the rapid phosphorylation of VASP. The phosphorylation of VASP was dependent on cell spreading, as VASP was expressed as a dephosphorylated protein in round adherent cells and was phosphorylated at the onset of changes in cell shape from round to spread cells. Immunofluorescence microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 45 publications
(68 reference statements)
0
26
0
Order By: Relevance
“…This possibility would be in agreement with the findings of Lambrechts et al (2000) and Harbeck et al, (2000), who showed that fully phosphorylated EVL and VASP bind less efficiently to Factin. The possibility that Ena/VASP phosphorylation plays a role in actin-based processes is supported by the observation that VASP phosphorylation directly correlates with spreading of neutrophils (Lawrence and Pryzwansky, 2001). Moreover, Mena phosphorylation is required for its function as negative regulator of cell motility in fibroblasts (Loureiro et al, 2002).…”
Section: Discussionmentioning
confidence: 63%
“…This possibility would be in agreement with the findings of Lambrechts et al (2000) and Harbeck et al, (2000), who showed that fully phosphorylated EVL and VASP bind less efficiently to Factin. The possibility that Ena/VASP phosphorylation plays a role in actin-based processes is supported by the observation that VASP phosphorylation directly correlates with spreading of neutrophils (Lawrence and Pryzwansky, 2001). Moreover, Mena phosphorylation is required for its function as negative regulator of cell motility in fibroblasts (Loureiro et al, 2002).…”
Section: Discussionmentioning
confidence: 63%
“…Furthermore, VASP, a member of the actin-binding protein family Drosophila Enabled/VASP, also plays a key role in cell motility (57). In neutrophils, VASP is phosphorylated by cGKI and colocalizes with F-actin in filopodia and focal adhesions during spreading, a time when cGMP levels are elevated (26). Fibroblasts deficient in mammalian homologue of Drosophila Enabled/VASP move faster than controls (58,59), suggesting that a possible mechanism for the increase in motility of cGKI Ϫ/Ϫ neutrophils is the reduced phosphorylation of VASP by cGKI.…”
Section: Chemotaxismentioning
confidence: 99%
“…For example, granule secretion of human neutrophils stimulated with fMLP or A23187 is associated with elevated cGMP levels and the phosphorylation of vimentin by cGKI (9,10,25). Similarly, during neutrophil adhesion and spreading, cGMP levels are elevated, and vasodilatorstimulated phosphoprotein (VASP), a membrane-associated focal adhesion protein, is phosphorylated by cGKI (26). Furthermore, when neutrophils are stimulated with LPS, p38 MAPK is phosphorylated upon accumulation of cGMP (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lamellipodial dynamics and behaviour are regulated by proteins of the Ena/VASP family, which are key controllers of actin polymerization in diverse cellular processes Coppolino et al, 2001;Jay, 2000;Krause et al, 2000;Laurent et al, 1999;Lawrence and Pryzwansky, 2001;Renfranz and Beckerle, 2002;Vasioukhin and Fuchs, 2001). Lamellipodial protrusion rate is directly correlated with the amount of Ena/VASP proteins within these projections (Rottner et al, 1999).…”
Section: Introductionmentioning
confidence: 99%